Applying intraoral scanner to residual ridge in edentulous regions: in vitro evaluation of inter-operator validity to confirm trueness - Akinori Tasaka; Yuuki Uekubo; Tomoharu Mitsui; Takao Kasahara; Takuya Takanashi; Shinya Homma; Satoru Matsunaga; Shinichi Abe; Masao Yoshinari; Yasutomo Yajima; Kaoru Sakurai; Shuichiro Yamashita (BMC, 2019)
Abstract Background The purpose of this study was to investigate the trueness of intraoral scanning of residual ridge in edentulous regions during in vitro evaluation of inter-operator validity. Methods Both edentulous maxillary and partially edentulous mandibular models were selected as a simulation model. As reference data, scanning of two models was performed using a dental laboratory scanner (D900, 3Shape A/S). Five dentists used an intraoral scanner (TRIOS 2, 3Shape A/S) five times to capture intraoral scanner data, and the "zig-zag" scanning technique was used. They did not have experience with using intraoral scanners in clinical treatment. The intraoral scanner data was overlapped with the reference data (Dental System, 3Shape A/S). Regarding differences that occurred between the reference and intraoral scanner data, the vertical maximum distance of the difference and the integral value obtained by integrating the total distance were analyzed. Results In terms of the maximum distances of the difference on the maxillary model, the means of five operators were as follows: premolar region, 0.30 mm; molar region, 0.18 mm; and midline region, 0.18 mm. The integral values were as follows: premolar region, 4.17 mm 2 ; molar region, 6.82 mm 2 ; and midline region, 4.70 mm 2 . Significant inter-operator differences were observed with regard to the integral values of the distance in the premolar and midline regions and with regard to the maximum distance in the premolar region, respectively. The maximum distances of the difference in the free end saddles on mandibular model were as follows: right side, 0.05 mm; and left side, 0.08 mm. The areas were as follows: right side, 0.78 mm 2 ; and left side, 1.60 mm 2 . No significant inter-operator differences were observed in either region. Conclusions The present study demonstrated satisfactory trueness of intraoral scanning of the residual ridge in edentulous regions during in vitro evaluation of inter-operator validity.